OP0061 Seizures in systemic lupus erythematosus: A prospective study of predictors and outcomes in a large, international, disease inception cohort. (23rd January 2014) - Hanly, J.G.
Abstract : Background: Seizures are a manifestation of neuropsychiatric (NP) SLE and occur in 6% to 51% of adult and pediatric patients. Objectives: To describe the frequency, attribution and outcome of seizure disorders and to identify clinical and laboratory predictors of their occurrence. Methods: An international, research network enrolled patients within 15 months of SLE diagnosis and performed annual assessments for up to 10 years. Seizures were recorded per ACR case definitions and decision rules determined their attribution. Additional information included clinical and demographic variables, global SLE disease activity (SLEDAI-2K), cumulative organ damage (SLICC/ACR Damage Index (SDI)), physician outcome (7 point Likert scale) and patient outcome using the mental (MCS) and physical (PCS) component summary scores of the SF-36. At enrollment lupus anticoagulant, anticardiolipin, anti-β2 glycoprotein-I, anti-ribosomal P and anti-NR2 glutamate receptor antibodies were measured. Statistical analyses included univariate and multivariate regression. Results: Of 1631 patients 89.4% were female and the mean (± SD) age was 35.0±13.4 years. The mean disease duration at enrollment was 5.6±4.8 months and the mean followup was 3.5±2.9 years. A total of 75/1631 (4.6%) patients had ≥1 seizure with the majority (79%) having a single event. In these 75 patients there were 91 seizures (66% generalized; 34% focal) of which 78/91 (86%) were attributed to SLE. The majority presented early in the disease course with a median (range) interval from the time of diagnosis of SLE to onset of first seizure of 0.14 (-0.50 – 7.57) years. There was a higher risk of seizures in those with African race/ethnicity (HR (CI): 1.97 (1.07-3.63); p=0.02) and lack of post-secondary education (1.97 (1.21-3.19); p<0.01). Higher SDI scores (without NP variables) were associated with an increased risk of subsequent seizures (SDI=1: 3.71 (1.38-9.95); SDI=2or3: 1.33 (0.27-6.46); SDI≥4: 6.44 (0.72-57.2); p=0.04). More patients with seizures attributed to SLE stopped taking anti-seizure drugs at the first followup assessment compared to patients with seizures attributed to non-SLE causes (19/66=29% vs. 2/12=17%) and similarly by the second followup assessment (32% vs. 11%). Using physician assessment, those seizures attributed to SLE were more likely to resolve (59/78, (76%)) compared to seizures attributed to non-SLE causes (7/13, (54%)). Using patient self-report the mean (± SD) MCS and PCS scores in patients with seizures and no other NP events was comparable to patients without NP events. Prior use of anti-malarial drugs in the absence of immunosuppressive agents was the most notable treatment effect on seizures (0.07 (0.01-0.66); p=0.02). There was no association with SLEDAI scores or between autoantibodies at enrollment with subsequent seizures. Conclusions: Most seizures in SLE patients are attributable to lupus in close proximity to the time of diagnosis of SLE. The risk of seizures is higher in patients of African race/ethnicity, lower educational status and organ damage outside of the nervous system. In the majority of cases the seizures resolve, do not require long-term anti-seizure medication and are not associated with a negative impact on mental or physical health-related quality of life. The association with lupus related therapies is complex but anti-malarial drugs may have a protective effect. Disclosure of Interest: None Declared